Primary pleural liposarcoma, pleomorphic variant (2014)
Primary pleural liposarcoma (PPL) is a rare tumor derived from primitive mesenchymal tissue. We report a case of a 49-year-old female patient complaining of thoracic pain and dyspnea for 3 months. The chest X-ray showed a left basal opacity of lobulated contours and the thoracic computer tomography (CT) scan revealed a left pleural collection/mass, of 18 HU density and passive pulmonary atelectasis. The patient was taken to surgery and the cytologic examination of the gelatinous mass found in the procedure confirmed the diagnosis of a pleomorphic variant of pleural liposarcoma. We emphasise in the importance of careful inspection of the origin of the tumor in the diagnostic images to allow accurate diagnosis. © Pioneer Bioscience Publishing Company.